Multilevel Optimization of the Semi-Open Impeller in a Centrifugal Pump - Papierski, Adam; Błaszczyk, Andrzej (Wydawnictwo Politechniki Łódzkiej ; Katedra Dynamiki Maszyn - Wydział Mechaniczny Politechniki Łódzkiej, 2011)
Full optimization task for the case of the semi-open impeller with straight blades, requires description of its' geometry by means of, at least, eighteen design variables. In the case of constant meridional cross-section, are required at least eight design variables. Solution of the task with such great vector of design variables requires much more time. One way to manage to obtain a solutions with great variety of design variables is comprehensive approach to the task depending on the partition into minor subtasks. After decomposing the optimization task, one should choose procedure of solving it. One of these procedures is parametric optimization, which is two-stage method of minimizing (maximizing). This optimization is carried on in two levels. On a lower level, multi-optimization of decomposed parts of the tasks, depending on design variables, is being held. The solution of the lower level is used in an upper level (coordinating level) to find optimal coordination variables. It has been shown that result of multilevel optimization and full task optimization is the same in limits of accepted accuracy of the objective functions' calculus. Time of the calculation for the multilevel optimization task is over four times shorter than undecomposed task time.
Keywords: semi-open impeller; multilevel optimization; wirnik półotwarty; optymalizacja wielopoziomowa